Nature and Nurture of Human Pain - Inna Belfer (Scientifica)
Humans are very different when it comes to pain. Some get painful piercings and tattoos; others can not stand even a flu shot. Interindividual variability is one of the main characteristics of human pain on every level including the processing of nociceptive impulses at the periphery, modification of pain signal in the central nervous system, perception of pain, and response to analgesic strategies. As for many other complex behaviors, the sources of this variability come from both nurture (environment) and nature (genes). Here, I will discuss how these factors contribute to human pain separately and via interplay and how epigenetic mechanisms add to the complexity of their effects.